Low birth weight may increase body fat mass in adult women with polycystic ovarian syndrome - Sonia Minooee; Fahimeh Ramezani Tehrani; Parvin Mirmiran; Fereidoun Azizi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Women engaged with polycystic ovarian syndrome (PCOS), as the commonest endocrine disorder, are known to have a specific type of adiposity. Birth weight is among different contributors reported to be responsible for this diversity. Objective: We aimed to compare the relation between birth weight and body fat mass (BFM)/ body lean mass (BLM) in PCOS and their age and body mass index (BMI) matched normal controls. Materials and Methods: In this case-control study, a total number of 70 reproductive aged women, diagnosed with PCOS and 70 age- BMI matched healthy women without hirsutism and/or ovulatory dysfunction were recruited., control group had no polycystic ovaries in ultrasonographic scans. A detailed history of birth weight was taken and was divided into the following categories: <2,500 (low birth weight, LBW) and 2,500-4,000 (normal birth weight; NBW). Results: Results showed that LBW prevalence was higher in women with PCOS than in controls (19.3% (27) vs. 15.7% (22)). Also body fat and lean mass (BFM, BLM) have increased in adult women with PCOS who were born underweight compared to their normal (19.8±9.05 vs. 12.9±4.5, p=0.001 and 48.9±6.9 vs. 43.2±5.8, p=0.004 respectively). Conclusion: Fetal birth weight influences on the adulthood obesity, BFM and BLM. This impact is different among women with and without PCOS